Effective bioprinting resolution in tissue model fabrication. Issue 11 (13th May 2019) - Miri, Amir K.; Mirzaee, Iman; Hassan, Shabir; Mesbah Oskui, Shirin; Nieto, Daniel; Khademhosseini, Ali; Zhang, Yu Shrike
Abstract : We compare current bioprinting technologies for their effective resolutions in the fabrication of micro-tissues towards construction of biomimetic microphysiological systems. Abstract : Recent advancements in bioprinting techniques have enabled convenient fabrication of micro-tissues in organ-on-a-chip platforms. In a sense, the success of bioprinted micro-tissues depends on how close their architectures are to the anatomical features of their native counterparts. The bioprinting resolution largely relates to the technical specifications of the bioprinter platforms and the physicochemical properties of the bioinks. In this article, we compare inkjet, extrusion, and light-assisted bioprinting technologies for fabrication of micro-tissues towards construction of biomimetic organ-on-a-chip platforms. Our theoretical analyses reveal that for a given printhead diameter, surface contact angle dominates inkjet bioprinting resolution, while nozzle moving speed and the nonlinearity of viscosity for bioinks regulate extrusion bioprinting resolution. The resolution of light-assisted bioprinting is strongly affected by the photocrosslinking behavior and light characteristics. Our tutorial guideline for optimizing bioprinting resolution would potentially help model the complex microenvironment of biological tissues in organ-on-a-chip platforms.